Pengaruh Karakteristik Wirausaha, Modal Usaha Dan Strategi Pemasaran Terhadap Perkembangan UMKM (Studi Kasus Pada Pelaku UMKM di Kecamatan Sangkapura Bawean) - Firdaus, Jannatul; Wahono, Budi; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to explain the characteristics of entrepreneurship, business capital and marketing strategies as well as knowing and partially explaining the characteristics of entrepreneurship, business capital and marketing strategies. This research method uses quantitative methods and the type of research is probability sampling using purposive sampling techniques. The sample for this research was 94 SMEs in Sangkapura Regency. The data analysis used is descriptive analysis, using SPSS 25 for Windows. The results of the research show that entrepreneurial characteristics, business capital and marketing strategies influence the development of SMEs among SMEs in Sangkapura Bawean Regency Keywords : Entrepreneurial Characteristics, Business Capital, Marketing Strategy, Development of SMEs